Peran dan Upaya Guru dalam Mencegah dan Menangani Kasus Bullying Pada Anak Tingkat Sekolah Dasar - Annisa Fardiyatul Muslimah; Danang Dwi Basuki (STAI AL-AMIN, 2023)
This research examines the role and efforts of teachers in preventing and dealing with bullying at the elementary school level. This research uses descriptive qualitative method. Data collection techniques used in this study are observation, interviews and documentation. The subject criteria in this study were all teachers who taught on average more than three years, totaling around six teachers. The data analysis techniques used in this study are data reduction, data presentation and inductive conclusion of data analysis. The results of the study show that the forms of bullying that occur in SD X Karawang city are verbal, physical and psychological bullying. The role and efforts of the teacher in preventing bullying are carried out in various ways, for example by means of group or classical direction, individual guidance, carrying out coaching activities at the beginning and end of the semester, if bullying is in the severe category the teacher will collaborate with parents in advising participants educate about bullying behavior. The teacher also provides input to the parents of students about the dangers of bullying behavior so that parents can always monitor their children's behavior.